The Effect of The Use of Audio Types of Learning Media on Students' Learning Motivation in Social Studies Subjects - Edo Suhariyanto (FKIP UNIVERSITAS LAMPUNG, 2020)
ABSTRACT One of the learning media that has been successfully developed to have a positive and significant impact on student motivation is the use of audio learning media. The formulation of the problem in this research is